Coulomb Enhanced Charge Transport in Semicrystalline Polymer Semiconductors. (20th September 2016) - Di Pietro, Riccardo; Nasrallah, Iyad; Carpenter, Joshua; Gann, Eliot; Kölln, Lisa Sophie; Thomsen, Lars; Venkateshvaran, Deepak; O'Hara, Kathryn; Sadhanala, Aditya; Chabinyc, Michael; McNeill, Christopher R.; Facchetti, Antonio; et al.
Abstract : Polymer semiconductors provide unique possibilities and flexibility in tailoring their optoelectronic properties to match specific application demands. The recent development of semicrystalline polymers with strongly improved charge transport properties forces a review of the current understanding of the charge transport mechanisms and how they relate to the polymer's chemical and structural properties. Here, the charge density dependence of field effect mobility in semicrystalline polymer semiconductors is studied. A simultaneous increase in mobility and its charge density dependence, directly correlated to the increase in average crystallite size of the polymer film, is observed. Further evidence from charge accumulation spectroscopy shows that charges accumulate in the crystalline regions of the polymer film and that the increase in crystallite size affects the average electronic orbitals delocalization. These results clearly point to an effect that is not caused by energetic disorder. It is instead shown that the inclusion of short range coulomb repulsion between charge carriers on nanoscale crystalline domains allows describing the observed mobility dependence in agreement with the structural and optical characterization. The conclusions that are extracted extend beyond pure transistor characterization and can provide new insights into charge carrier transport for regimes and timescales that are relevant to other optoelectronic devices. Abstract : The charge density dependence of the charge carrier mobility in semicrystalline polymers is shown to be directly correlated to the increase in crystallite size in the polymer film. The effect is not caused by energetic disorder and can be explained if the morphology of semicrystalline polymers and the effect of electron electron interaction is explicitly taken into account.